History and mythology of the Aztecs : the Codex Chimalpopoca - Bierhorst, John (University of Arizona Press, 1992)
"One of the great documents of colonial Mexico, the Codex Chimalpopoca chronicles the rise of Aztec civilization and preserves the mythology on which it was based - supplying a richness of detail unmatched by any other native-language source. Specifically, its two complementary texts, Annals of Cuauhtitlan and Legend of the Suns, record the pre-Cortesian history of the Valley of Mexico together with first-hand versions of that region's myths. Of particular interest are the stories of the hero-god Quetzalcoatl, for which the Chimalpopoca is the premier source."--BOOK JACKET. "John Bierhorst's work represents the first major scholarship on the Codex Chimalpopoca in more than forty years. His is the first edition in English and the first in any language to include the complete text of the Legend of the Suns."--BOOK JACKET. "The precise, readable translation - fully indexed - will not only contribute to the study of Aztec history and literature but will make the codex an indispensable reference for Aztec cultural topics, including land tenure, statecraft, the role of women, the tribute system, warfare, and human sacrifice."--Jacket.